Tactics of Administration of Patients with Hemorrhagic Syndrome with Chronic Polyposis - Saydullayevich , Makhmonov Lutfulla; Yakubovich , Isamov Aziz; Utkurovich, Dadajonov Uktam; Haydarovna , Mamatkulova Feruza (Miasto Przyszłości, 2023)
The article describes the phenotypic characteristics of 3 patients with various types of gastrointestinal lesions in Crohn's disease, the path to diagnosis verification, and a dynamic assessment of therapeutic tactics. The complexity of the differential diagnosis of inflammatory bowel diseases, despite the use of additional research methods, is determined by the commonality of clinical manifestations. Choosing the correct treatment strategy at any stage of the disease course should be considered an essential component of successful patient management.